Effectiveness of stop‐smoking medications: findings from the International Tobacco Control (ITC) Four Country Survey. (14th August 2012) - Kasza, Karin A.; Hyland, Andrew J.; Borland, Ron; McNeill, Ann D.; Bansal‐Travers, Maansi; Fix, Brian V.; Hammond, David; Fong, Geoffrey T.; Cummings, K. Michael
Abstract Aim To evaluate the population effectiveness of stop‐smoking medications while accounting for potential recall bias by controlling for quit attempt recency. Design Prospective cohort survey. Setting United Kingdom, Canada, Australia and the United States. Participants A total of 7436 adult smokers (18+ years) selected via random digit dialling and interviewed as part of the International Tobacco Control Four Country Survey (ITC‐4) between 2002 and 2009. Primary analyses utilized the subset of respondents who participated in 2006 or later (n = 2550). Measurements Continuous abstinence from smoking for 1 month/6 months. Findings Among participants who recalled making a quit attempt within 1 month of interview, those who reported using varenicline, bupropion or nicotine patch were more likely to maintain 6‐month continuous abstinence from smoking compared to those who attempted to quit without medication [adjusted odds ratio (OR) 5.84, 95% confidence interval (CI) (2.12–16.12), 3.94 (0.87–17.80), 4.09 (1.72–9.74), respectively]; there were no clear effects for oral NRT use. Those who did not use any medication when attempting to quit tended to be younger, to be racial/ethnic minorities, to have lower incomes and to believe that medications do not make quitting easier. Conclusions Consistent with evidence from randomized controlled trials, smokers in the United Kingdom, Canada, Australia and the United States are more likely to succeed in quit attempts if they use varenicline, bupropion or nicotine patch. Previous population studies that failed to find an effect failed to control adequately for important sources of bias.